Improving albumen thermal stability using succinylation reaction with octenyl succinic anhydride. (November 2016) - Kulchaiyawat, Charlwit; Wang, Tong; Han, Zhaopeng
Abstract: Modification of egg white proteins with octenyl succinic anhydride (OSA) was investigated for improving thermal stability of the albumen. The reaction occurred at pH 8.5 for 3 h at 35 °C, and the degree of reaction was quantified by determining the amine group quantity. The effect of sonication pretreatment and OSA addition level on degree of reaction and product heat stability were evaluated, and they were found to have significant impact on product quality. Three different egg white materials were tested; they were rehydrated commercial egg white protein (EWP), fresh egg white (FEW), and commercial de-glucosed egg white (CFEW). They behaved differently toward this chemical modification. At 5% OSA addition, CFEW did not show significant change in amine group concentration, but at 4% OSA use EWP and FEW had 30–40% reduction of amine group. The use of sonication for the FEW at 4% OSA led to 60% amine reduction. At higher temperature of thermal stability evaluation, 95 °C compared to 75 °C, the sonicated and 10% OSA succinylated FEW showed significant stability improvement with a turbidity 30% of that of the control. For the 4% OSA succinylated EWP, its turbidity was only 20% of the control. Therefore, thermal stability improvement was achieved by OSA modification of egg albumen. Highlights: Succinylation of egg white protein with OSA can be feasibly achieved. The amphiphilic nature of the OSA is shown to provide the protein with thermal stabilization. The type of egg white used influenced the reaction and stability improvement. This modification may allow egg white protein's use in thermally stabilized liquid products.